A self-repairable super-hydrophobic fabric and its preparation method and application

By using in-situ growth method to form a zirconium phosphate layer during the preparation of superhydrophobic fabrics and performing low surface energy treatment in the modified solution, the problem that existing superhydrophobic fabrics cannot be self-repaired is solved, and the self-repair and versatility of the fabrics are achieved.

CN116180432BActive Publication Date: 2025-03-11SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211594967.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-13
Publication Date
2025-03-11
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

The existing superhydrophobic fabric preparation methods cannot be supplemented and self-repaired when superhydrophobic structure is lost, which limits its application scope.

Method used

After impregnating the substrate in a zirconium oxychloride solution, adding phosphoric acid and surfactant for stirring, an initial solution was obtained, and grown in situ in the reactor to form a substrate with zirconium phosphate grown on the surface, and then low surface energy treatment was performed in the modified solution to produce a self-healing superhydrophobic fabric.

Benefits of technology

It realizes the self-healing function of superhydrophobic fabrics, maintains the original properties and diversified functions of the fabrics, and has acid and alkali resistance, superhydrophobicity and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116180432B_ABST
    Figure CN116180432B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of super-hydrophobic coatings, and more particularly to a self-repairable super-hydrophobic fabric and its preparation method and application, the preparation method comprising the steps of: mixing and stirring a substrate, a zirconium oxychloride solution, phosphoric acid, and a surfactant to obtain an initial solution; the initial solution reacts so that zirconium phosphate is formed by in-situ growth on the surface of the substrate, and a substrate with zirconium phosphate grown on the surface is obtained; then it is immersed in a modified solution for low surface energy treatment to obtain a self-repairable super-hydrophobic fabric. The present invention utilizes an in-situ growth method, with zirconium phosphate as the final grown product, so that zirconium phosphate is crystallized on the surface with the substrate surface as the growth center, grows naturally, and achieves close combination; and the obtained functional particles are relatively small, usually micron-sized or nano-sized particles, effectively avoiding compatibility problems, thereby enhancing the bonding force between zirconium phosphate and the substrate; while retaining the original properties of the substrate, the product functions are diversified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of super-hydrophobic coatings, and in particular to a self-repairable super-hydrophobic fabric and a preparation method and application thereof. Background Art

[0002] At present, there are many methods for preparing superhydrophobic materials, but there are only a few methods that can be put into large-scale use in a real sense. Superhydrophobic products that meet market demand usually need to meet the following three points:

[0003] First point: The preparation method is simple, usually only one or two processes are required to complete, and the process flow usually does not require more complicated equipment to meet the needs of mass production.

[0004] The second point: The raw materials are green and safe, and there is no possibility of releasing or containing toxic substances.

[0005] The third point: long service life, reducing replacement frequency and saving costs.

[0006] However, existing methods for preparing superhydrophobic products usually cannot meet these three requirements. Some methods may even change the properties of the material during use and fail to retain the advantages of the material itself. For example, some polymers adhere to the surface of the spun fabric, which can easily make the fabric hard or reduce its air permeability. Moreover, most preparation methods can only provide strong superhydrophobicity that can resist changes in the external environment, but cannot replenish or self-repair when the superhydrophobic structure is damaged. Therefore, they are easily restricted in application.

[0007] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0008] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a self-repairable super-hydrophobic fabric and a preparation method and application thereof, aiming to solve the problem that the super-hydrophobic fabric prepared by the existing preparation method cannot be replenished and self-repaired when the super-hydrophobic structure is lost.

[0009] The technical solution of the present invention is as follows:

[0010] A method for preparing a self-repairable super-hydrophobic fabric comprises the following steps:

[0011] After the substrate is immersed in the zirconium oxychloride solution, phosphoric acid is added and stirred, and then a surfactant is added and stirred continuously to obtain an initial solution;

[0012] Allowing the initial solution to grow in situ to obtain a substrate with zirconium phosphate grown on the surface;

[0013] The substrate with zirconium phosphate grown on the surface is immersed in a modification solution for low surface energy treatment to obtain a self-repairable super-hydrophobic fabric.

[0014] The method for preparing the self-repairable super-hydrophobic fabric, wherein the zirconium oxychloride solution is prepared by mixing zirconium oxychloride and water; the volume fraction of the zirconium oxychloride solution is 15-25%.

[0015] The method for preparing the self-repairable super-hydrophobic fabric, wherein the molar ratio of the phosphorus element in the phosphoric acid to the zirconium element in the zirconium oxychloride solution is 1.2-1.5.

[0016] The method for preparing the self-repairable super-hydrophobic fabric, wherein the in-situ growth condition is in-situ growth at a temperature of 100-120° C. for 18-24 hours.

[0017] The method for preparing the self-repairable super-hydrophobic fabric, wherein the surfactant is selected from one or more of Tween-80, aniline, and sodium dodecyl sulfate.

[0018] The method for preparing the self-repairable super-hydrophobic fabric, wherein the concentration of the modified solution is (1g-1.5g) / 100mL; the volume of the surfactant accounts for 0.5-1% of the total volume of the initial solution.

[0019] The method for preparing the self-repairable super-hydrophobic fabric, wherein the solvent of the modified solution is ethyl acetate; the solute of the modified solution is selected from one of octadecylamine, octadecyltrimethoxysilane, hexadecyltriethoxysilane and n-dodecyltriethoxysilane.

[0020] The method for preparing the self-repairable super-hydrophobic fabric, wherein after the low surface energy treatment, the method further comprises:

[0021] The substrate with zirconium phosphate grown on the surface after low surface energy treatment is washed with alcohol and then dried at 100-110°C.

[0022] A self-repairable super-hydrophobic fabric is prepared by utilizing the preparation method of the self-repairable super-hydrophobic fabric.

[0023] An application of a self-repairable super-hydrophobic fabric, wherein the self-repairable super-hydrophobic fabric is used for oil-water separation.

[0024] Beneficial effects: The present invention provides a self-repairable super-hydrophobic fabric and a preparation method and application thereof. The preparation method comprises the steps of: continuously mixing and stirring a substrate, a zirconium oxychloride solution, phosphoric acid, and a surfactant to obtain an initial solution; reacting the initial solution to form zirconium phosphate in situ on the surface of the substrate to obtain a substrate with zirconium phosphate grown on the surface; immersing the substrate with zirconium phosphate grown on the surface in a modified solution for low surface energy treatment to obtain a self-repairable super-hydrophobic fabric. The present invention utilizes an in-situ growth method and uses zirconium phosphate as the final growth product, so that the zirconium phosphate takes the surface of the substrate as the growth center, crystallizes on the surface, grows naturally, and achieves close bonding; and the functional particles obtained are relatively small, usually micron-level or nano-level particles, which effectively avoid compatibility problems, thereby enhancing the bonding force between the zirconium phosphate and the substrate; while retaining the original properties of the substrate, the product functions are diversified; and the preparation method obtains a super-hydrophobic fabric with acid and alkali resistance, super-hydrophobicity, mechanical properties, and self-repairability, that is, the zirconium phosphate layered structure obtained by the in-situ growth method is intricate, and after modification, the hydrophobic substance can be replenished in time when it is lost. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The present invention is a process flow diagram of a method for preparing a self-repairable super-hydrophobic fabric;

[0026] Figure 2 This is a schematic diagram of the process of preparing a self-repairable super-hydrophobic fabric according to Example 1 of the present invention;

[0027] Figure 3 This is a SEM microstructure diagram of the self-repairable super-hydrophobic fabric in Example 1 of the present invention;

[0028] Figure 4 This is a SEM microstructure image of the untreated fabric in Comparative Example 1 of the present invention;

[0029] Figure 5 This is a SEM microstructure image of the fabric after zirconium phosphate is produced in Comparative Example 2 of the present invention without adding a surfactant. DETAILED DESCRIPTION

[0030] The present invention provides a self-repairing super-hydrophobic fabric and a preparation method and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] In the embodiments and the scope of the patent application, unless the text specifically defines the article, "a", "an", "the" and "the" may also include plural forms. If there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features.

[0032] It should be further understood that the wording "comprising" used in the specification of the present invention refers to the presence of the features, integers, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or their groups. The wording "and / or" used herein includes all or any unit and all combinations of one or more associated listed items.

[0033] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.

[0034] Zirconium phosphate compounds (Zr(HPO4)2.H2O(α-ZrP), Zr(PO4)(H2PO4)·2H2O(γ-ZrP), Zr(HPO4)2·6H20(θ-ZrP), etc.) are a new type of multifunctional material that has developed rapidly in recent years. They have the characteristics of layered compounds, good crystal form, and the preparation method is very simple. The conditions are mild and do not require high temperature and high pressure environments. The compounds have a certain acid and alkali resistance, high stability, excellent mechanical properties and weather resistance.

[0035] Based on this, please refer to Figure 1 The present invention provides a method for preparing a self-repairable super-hydrophobic fabric, comprising the steps of:

[0036] Step S10: mixing and stirring the substrate, zirconium oxychloride solution, phosphoric acid, and surfactant to obtain an initial solution;

[0037] Step S20: the initial solution reacts to form zirconium phosphate in situ on the surface of the substrate, thereby obtaining a substrate with zirconium phosphate grown on the surface;

[0038] Step S30: immersing the substrate with zirconium phosphate grown on the surface into a modification solution for low surface energy treatment to obtain a self-repairable super-hydrophobic fabric.

[0039] The present invention adopts zirconium phosphate as the final product of the in-situ growth method, which has the common properties of layered compounds, high chemical stability, excellent heat resistance and acid and alkali resistance, can be used for a long time, and also has the ion exchange performance of ion resin and the selective adsorption performance of zeolite; and has the advantages of mild preparation conditions, simple preparation method, low toxicity of preparation raw materials, and green safety; and the layered structure of zirconium phosphate with a large specific surface area is basically not affected after the guest is introduced into the structure, and maintains the original state.

[0040] In this embodiment, the in-situ growth method is used to take the surface of the substrate as the growth center, and zirconium phosphate is obtained by in-situ growth, and then the modified solution is used for low surface treatment, and finally a self-repairing super-hydrophobic fabric is obtained. Since zirconium phosphate itself has strong mechanical properties, and its layered structure can load a large amount of solutes in the modified solution, the obtained super-hydrophobic fabric has the advantage of being strong; at the same time, since zirconium phosphate is a mesoporous porous material, part of the modified solution can be stored inside it. When the hydrophobic substance on the surface of the fabric is destroyed, the fabric will become hydrophilic, and the surface energy is low, and it is in a thermodynamically unstable state. At this time, the modified solution in the zirconium phosphate pore will diffuse to the fabric surface to reduce energy and realize the self-repair function of the super-hydrophobic fabric. The super-hydrophobic fabric prepared by combining the advantages of in-situ growth and the properties of zirconium phosphate retains the original air permeability and flexibility of the fabric.

[0041] Specifically, after the substrate is immersed in a zirconium oxychloride solution, phosphoric acid is added and stirred, and then a surfactant is added to continue stirring to obtain an initial solution; the initial solution is placed in a reactor for in-situ growth to obtain a substrate with zirconium phosphate grown on the surface; the substrate with zirconium phosphate grown on the surface is immersed in a modified solution for low surface energy treatment to obtain a self-repairable super-hydrophobic fabric. The above-mentioned preparation method does not involve any toxic reagents during the process, and the reaction conditions are relatively mild. Except for in-situ growth in the reactor, the others are all carried out at room temperature. The obtained self-repairable super-hydrophobic fabric has an oil-water separation efficiency of more than 99%, and can also maintain an oil-water separation effect of more than 99% efficiency in an acid-base or salt environment. The self-repairable super-hydrophobic fabric has the ability to self-repair after oxidation, and within a certain range, the repair time is shorter as the temperature increases, and the self-repairable super-hydrophobic fabric can maintain the original softness and breathability.

[0042] In some embodiments, the zirconium oxychloride solution is prepared by mixing zirconium oxychloride and water; the volume fraction of the zirconium oxychloride solution is 15-25%. Since the subsequent in-situ growth requires a large amount of zirconium oxychloride to participate in the reaction so that a dense zirconium phosphate layer is formed on the surface of the substrate, it is necessary to ensure that the volume fraction of the zirconium oxychloride solution is between 15-25%.

[0043] In some embodiments, the molar ratio of phosphorus in the phosphoric acid to zirconium in the zirconium oxychloride solution is 1.2-1.5, so that phosphoric acid and zirconium oxychloride can fully react during in-situ growth, crystallize on the substrate surface, grow naturally, and obtain zirconium phosphate on the substrate surface.

[0044] In some embodiments, the in-situ growth condition is to grow in-situ at a temperature of 100-120° C. for 18-24 hours. When the reaction is carried out within this temperature and time range, the in-situ growth effect is more complete.

[0045] In a preferred embodiment, the in-situ growth condition is to react at a temperature of 100° C. for 24 hours to produce zirconium phosphate on the surface of the substrate.

[0046] In some embodiments, in step S20, after the initial solution is reacted to form zirconium phosphate in situ on the surface of the substrate, the substrate with zirconium phosphate grown on the surface is placed in deionized water to remove excess white precipitate from the surface, and then dried at room temperature.

[0047] In some embodiments, the surfactant is selected from one or more of Tween-80, aniline, and sodium dodecyl sulfate. Surfactants are used to refine the surface structure, resulting in antennae and structural changes.

[0048] In some embodiments, the volume of the surfactant accounts for 0.5-1% of the total volume of the initial solution; the purpose of adding the surfactant to the reaction matrix is ​​to change the interface state of the solution, thereby changing the state of subsequent growth of zirconium phosphate on the fabric surface, thereby optimizing the surface structure.

[0049] In a preferred embodiment, the surfactant is Tween-80.

[0050] In some embodiments, the concentration of the modified solution is (1g-1.5g) / 100mL. The amount of the modified solution used is most suitable for forming a modified monomolecular film on the surface of the inorganic powder. If the amount is insufficient, the surface of the powder particles cannot be fully covered and activated; if the amount is too much, it will not only increase the cost, but also make the excess modified solution free in the filling system, affecting the performance of the composite material.

[0051] In some embodiments, the solvent of the modified solution is ethyl acetate; the solute of the modified solution is selected from one of octadecylamine, octadecyltrimethoxysilane, hexadecyltriethoxysilane, and n-dodecyltriethoxysilane; these modified solutions have lower toxicity and better treatment effect.

[0052] In a preferred embodiment, the modified solution is a mixture of ODA powder and ethyl acetate solvent. The surface of zirconium phosphate contains a large number of hydroxyl groups, which react with the amine groups of ODA to graft ODA onto the surface of zirconium phosphate; of course, selecting octadecyltrimethoxysilane, hexadecyltriethoxysilane, and n-dodecyltriethoxysilane as the solvent of the modified solution can also achieve the same effect.

[0053] In some embodiments, in step S30, after the low surface energy treatment, the process further comprises: washing the substrate with zirconium phosphate grown on the surface after the low surface energy treatment with alcohol, and then drying the substrate at 100-110°C.

[0054] In some embodiments, since zirconium phosphate is often used as a composite substance of fireproof materials, the present invention can also add fireproof components during the preparation process to give the fabric fireproof properties.

[0055] In addition, the present invention also provides a self-repairable super-hydrophobic fabric, which is prepared by the preparation method of the self-repairable super-hydrophobic fabric as described above.

[0056] The self-repairable super-hydrophobic fabric prepared by the above-mentioned preparation method has the softness and air permeability of the fabric itself, and obtains super-hydrophobic properties on the basis of retaining these properties, and can perform self-cleaning and oil-water separation to achieve multifunctionality; and the oil-water separation efficiency of the self-repairable super-hydrophobic fabric is above 99%.

[0057] The present invention also provides an application of a self-repairable super-hydrophobic fabric, wherein the self-repairable super-hydrophobic fabric is used for oil-water separation; when the self-repairable super-hydrophobic fabric is used for oil-water separation, its oil-water separation efficiency can reach more than 99%, and the same oil-water separation effect as that under normal conditions is maintained under acidic, alkaline or salt environments; after the self-repairable super-hydrophobic fabric is oxidized, it has a self-repairing ability.

[0058] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0059] Example 1

[0060] This embodiment provides a self-repairable super-hydrophobic fabric, and the preparation method thereof comprises the steps of:

[0061] Step S1: Immerse the sample fabric in the zirconium oxychloride solution for 15 minutes, then add 40 ml of phosphoric acid while stirring, and then use a magnetic stirrer to stir the solution until the colloid is roughly dissolved and becomes a whitish solution, then add a small amount of Tween-80 (accounting for 0.8% of the total volume of the initial solution) and continue stirring for 10 minutes to obtain an initial solution; wherein the zirconium oxychloride solution is prepared by 5.5 g of zirconium oxychloride and 10.5 ml of water.

[0062] Step S2: placing the initial solution in a reactor and performing in-situ growth at 100° C. for 24 hours to obtain a fabric with zirconium phosphate grown on the surface; after the in-situ growth is completed, cleaning the excess white precipitate on the surface of the fabric in deionized water and drying at room temperature.

[0063] Step S3: Immerse the substrate with zirconium phosphate grown on the surface in a modified solution (ODA powder + ethyl acetate solvent, 1 g / 100 ml) for 10 hours for low surface energy treatment, and finally take it out for alcohol washing and drying at 100°C to obtain a self-repairable superhydrophobic fabric.

[0064] Specifically, the process of preparing the self-repairable super-hydrophobic fabric in this embodiment is as follows: Figure 2 As shown, the fabric was immersed in zirconium oxychloride solution for 15 minutes; after immersion, phosphoric acid and Tween-80 were added and mixed evenly, and then added into a reactor and reacted at 100°C for 24 hours; after the reaction, a layered zirconium phosphate was generated on the surface of the fabric; then the fabric was further modified with octadecylamine to obtain superhydrophobic properties, and the final results showed that water droplets could not wet the surface.

[0065] In this embodiment, the self-repairable super-hydrophobic fabric has a low surface energy and a strong, repairable micro-nano composite structure. The SEM microstructure of the self-repairable super-hydrophobic fabric prepared in this embodiment is shown in FIG. Figure 3 As shown, the contact angle is approximately 162°.

[0066] Example 2

[0067] The difference between this embodiment and embodiment 1 is that the reaction time and reaction temperature of the in-situ growth are different, as shown in Table 1 and Table 2:

[0068] Table 1 Effect of reaction time on contact angle of superhydrophobic fabric

[0069] Reaction temperature (℃) Reaction time (h) Contact angle (°) 100 6 120 100 12 136 100 18 158

[0070] Table 2 Effect of reaction temperature on contact angle of super hydrophobic fabric

[0071] Reaction temperature (℃) Reaction time (h) Contact angle (°) 60 24 110 80 24 140 120 24 161

[0072] Comparative Example 1

[0073] Untreated fabric is provided. The SEM microstructure of the untreated fabric is shown in Figure 4 shown.

[0074] Comparative Example 2

[0075] The difference between Comparative Example 2 and Example 1 is that the fabric after zirconium phosphate production is produced without adding surfactant. The SEM microstructure of the fabric after zirconium phosphate production is produced without adding surfactant is as follows: Figure 5 As shown, the flaky micron-scale or even nano-scale structure generated on its surface is composed of a large number of zirconium phosphate monomers, and zirconium phosphate is the functional particle.

[0076] By comparing the SEM microstructure images of Example 1 and Comparative Examples 1-2, it can be seen that the formation of zirconium phosphate increases the surface roughness of the fabric, and the surfactant makes this effect more obvious, thereby increasing the contact angle.

[0077] In summary, the present invention provides a self-repairable super-hydrophobic fabric and a preparation method and application thereof. The preparation method comprises the steps of: immersing a substrate in a zirconium oxychloride solution, adding phosphoric acid and stirring, and then adding a surfactant and continuing to stir to obtain an initial solution; placing the initial solution in a reactor for in-situ growth to obtain a substrate with zirconium phosphate grown on the surface; immersing the substrate with zirconium phosphate grown on the surface in a modified solution for low surface energy treatment to obtain a self-repairable super-hydrophobic fabric. The present invention utilizes an in-situ growth method and uses zirconium phosphate as the final growth product, so that the zirconium phosphate takes the surface of the substrate as the growth center, crystallizes on the surface, grows naturally, and achieves close bonding; and the functional particles obtained are relatively small, usually micron-level or nano-level particles, which effectively avoid compatibility problems, thereby enhancing the bonding force between the zirconium phosphate and the substrate; while retaining the original properties of the substrate, the product functions are diversified; and the preparation method obtains a super-hydrophobic fabric with acid and alkali resistance, super-hydrophobicity, mechanical properties, and self-repairability, that is, the zirconium phosphate layered structure obtained by the in-situ growth method is intricate, and after modification, the hydrophobic substance can be replenished in time when it is lost.

[0078] That is, the present invention in-situ grows zirconium phosphate on the fabric surface under mild reaction conditions, and the layered structure of zirconium phosphate causes the surface roughness to change, resulting in a stable super-hydrophobic state after modification, and the characteristics of the layered structure give it super-hydrophobic anti-oxidation self-repairing properties. The addition of an appropriate amount of surfactant can improve the surface micro-nano composite structure, making the super-hydrophobic effect more significant.

[0079] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a self-repairable super-hydrophobic fabric, characterized in that: Includes steps: After the fabric is immersed in the zirconium oxychloride solution, phosphoric acid is added and stirred, and then a surfactant is added and stirred continuously to obtain an initial solution; The initial solution reacts to form zirconium phosphate by in-situ growth on the surface of the fabric, thereby obtaining a fabric with zirconium phosphate grown on the surface; The fabric with zirconium phosphate grown on the surface is immersed in a modification solution for low surface energy treatment to obtain a self-repairable super-hydrophobic fabric; The zirconium oxychloride solution is prepared by mixing zirconium oxychloride and water; the volume fraction of the zirconium oxychloride solution is 15-25%; The surfactant is Tween-80; The volume of the surfactant accounts for 0.5-1% of the total volume of the initial solution; The in-situ growth conditions are in-situ growth at a temperature of 100-120° C. for 18-24 hours.

2. The method for preparing a self-repairable super-hydrophobic fabric according to claim 1, characterized in that: The molar ratio of phosphorus in the phosphoric acid to zirconium in the zirconium oxychloride solution is 1.2-1.

5.

3. The method for preparing a self-repairable super-hydrophobic fabric according to claim 1, characterized in that: The concentration of the modified solution is (1g-1.5g) / 100mL.

4. The method for preparing a self-repairable super-hydrophobic fabric according to claim 1, characterized in that: The solvent of the modified solution is ethyl acetate; the solute of the modified solution is selected from one of octadecylamine, octadecyltrimethoxysilane, hexadecyltriethoxysilane and n-dodecyltriethoxysilane.

5. The method for preparing a self-repairable super-hydrophobic fabric according to claim 1, characterized in that: After the low surface energy treatment, the method further comprises: The fabric with zirconium phosphate grown on the surface after low surface energy treatment is washed with alcohol and then dried at 100-110°C.

6. A self-repairable super-hydrophobic fabric, characterized in that: The self-repairable super-hydrophobic fabric is prepared by the preparation method of any one of claims 1 to 5.

7. An application of the self-repairable super-hydrophobic fabric as claimed in claim 6, characterized in that: The self-repairable superhydrophobic fabric is used for oil-water separation.